ASSESSMENT OF PREVALENCE OF BREAST CANCER IN PATIENTS WITH OBESITY AND EVALUATING BENEFITS OF STATIN THERAPY IN BREAST CANCER TREATMENT - ZAINAB LOKHANDWALA; FAHIM KHAN; SRINIVAS NAYAK SP; GUNOSINDHU CHAKRABORTHY (Asian Journal of Pharmaceutical and Clinical Research, 2025)
ABSTRACT Objective: Assessing the prevalence of breast cancer and evaluating the feasibility of statins as adjunct therapy in breast cancer management as well as their effectiveness in reducing recurrence. Methods: A bi-directional study was conducted over 6 months at Parul Sevashram Hospital, India, involving 102 breast cancer patients. Data on demographics, body mass index (BMI), cancer subtypes, statin usage (type, dose, duration), adjuvant therapy integration, and recurrence were collected through medical records and organized discussions. Analytical methods comprised of Pearson-Chi square tests to assess associations between statin continuation and recurrence. Results: Among 102 patients, 46.07% (n=47) possessed a normal BMI, whereas 53.66% (n=55) were pre-obese/obese (BMI≥25). Invasive ductal carcinoma (65%, n=63) was the most prevalent subtype. Of 83 patients assessed for statin use, 38.55% (n=32) were prescribed statins (atorvastatin: 62.5%, rosuvastatin: 31.25%, simvastatin: 6.25%), primarily for hypercholesterolemia (71.87% obese patients). Among statin users, 71.87% (n=23) continued therapy as adjuvant treatment. Recurrence occurred in 21.74% (n=5) of statin-continuation patients versus 66.67% (n=6) in the discontinuation group (χ²=3.97, p=0.046). Lipophilic statins (atorvastatin, simvastatin) showed stronger recurrence reduction (78.26% non-recurrence) compared to discontinuation (33.33%). Conclusion: Statin continuation as adjuvant therapy significantly reduced breast cancer recurrence, particularly in obese patients, with lipophilic statins (e.g., atorvastatin) demonstrating notable efficacy. The study highlights statins’ potential dual role in managing hyperlipidemia and cancer outcomes, emphasizing their integration into breast cancer care for high-BMI populations. Further large-scale trials are needed to validate optimal dosing, duration, and long-term survival benefits.